2021
DOI: 10.1186/s12884-021-03632-9
|View full text |Cite
|
Sign up to set email alerts
|

Patient perceptions, opinions and satisfaction of telehealth with remote blood pressure monitoring postpartum

Abstract: Background Our aim was to conduct a post participation survey of respondent experiences with in-home remote patient monitoring via telehealth for blood pressure monitoring of women with postpartum hypertension. We hypothesized that the in-home remote patient monitoring application will be implemented with strong fidelity and have positive patient acceptability. Methods This analysis was a planned secondary analysis of a non-randomized controlled tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…In a survey of 128 patients conducted in the United States, postpartum women perceived a telehealth technology remote intervention as a safe and easy-to-use method, with an acceptable burden of care and an overall satisfactory method of monitoring blood pressure in the postpartum period [ 116 ]. A survey conducted in Belgium reported that 80% of midwives and 67% of obstetricians who used remote blood pressure monitoring in pregnancy perceived digital technologies as an important component of prenatal monitoring [ 117 ].…”
Section: Blood Pressure Measurement During Pregnancymentioning
confidence: 99%
“…In a survey of 128 patients conducted in the United States, postpartum women perceived a telehealth technology remote intervention as a safe and easy-to-use method, with an acceptable burden of care and an overall satisfactory method of monitoring blood pressure in the postpartum period [ 116 ]. A survey conducted in Belgium reported that 80% of midwives and 67% of obstetricians who used remote blood pressure monitoring in pregnancy perceived digital technologies as an important component of prenatal monitoring [ 117 ].…”
Section: Blood Pressure Measurement During Pregnancymentioning
confidence: 99%
“…The remote collection of blood pressures has been discussed as being acceptable for patients receiving clinical care (e.g. outside of a research setting), in populations such as pregnant or recently pregnant women, and individuals with heart failure [40][41][42]. However, there is a lack of evidence regarding acceptability within clinical trials and older adults.…”
Section: Outcome Assessment Adaptationsmentioning
confidence: 99%
“…Pandemic-related changes have suggested TH to be a valuable tool to support self-management of chronic conditions like diabetes (Kirby et al, 2021;Ramaswamy, 2020;Thomas et al, 2021). A prepandemic review of the literature suggested that TH visits were more effective when combined with IP visits to build rapport and connectivity, which lays the foundation for strong providerpatient relationship (Dixon et al, 2020;Su et al, 2016).…”
Section: Telehealth and Diabetes Self-managementmentioning
confidence: 99%